Integrating Value Co-Creation, Experiential Learning, and University Signaling to Strengthen Graduate Employability - Juanna, Andi; Rizan, Mohammad; Wibowo, Ferry Setyo (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
Digital transformation and changing labor-market expectations have repositioned universities as strategic ecosystems that co-create value with students, industries, alumni, and society. This study conducts a Systematic Literature Review to examine how Value-Based Marketing, Experiential Learning, and Signaling Theory are integrated to strengthen graduate employability in higher education. Guided by the PRISMA 2020 protocol, articles were collected from ScienceDirect, Emerald Insight, and MDPI databases during the 2020–2026 period. From 734 initial records, 51 studies met the inclusion criteria and were analyzed through bibliometric mapping and thematic synthesis using VOSviewer. The findings reveal four dominant themes: value co-creation and service logic, experiential learning and student engagement, university reputation and signaling mechanisms, and career readiness and employability outcomes. The review shows that graduate employability is not merely an individual achievement but the result of a collaborative value ecosystem involving institutional strategy, meaningful learning experiences, industry engagement, and credible reputation signals. This study contributes an integrative perspective on how value logic, learning experience, and institutional signaling create sustainable competitive advantage for universities in the Industry 5.0 era